AMERICAN WOMEN'S STRIVE FOR SOCIAL JUSTICE IN CLINT EASTWOOD'S CHANGELING MOVIE (2008) : A FEMINIST APPROACH - OKTARINI , KHOLIDAH LAILA (2010)
The major problem of this study is women's strive for social justice which is reflected in Changeling. The aim of the study is to analyze the movie based on the structural elements and to analyze the film based on the feminist theory. In analyzing Changeling film, the writer uses the qualitative method and Feminist Approach. The data sources are primarily data source, which uses the Changeling's script written by Clint Eastwood in 2008, and secondary data source is biography, an essay, comment, historical information and other relevant information. The method of collecting data is library research. The technique for analyzing is descriptive analysis. The outcome of the study shows the following conclusions. Firstly, based on the structural analysis, it is indicated that each of narrative and technical element of movie is related into solid unity. Secondly, based on feminist, it is depicted that it is hard for women to strive for social justice. The last, the author wants to assert that everybody has strength and weakness regardless the power to be someone he or she wants.